2012
DOI: 10.1371/journal.pone.0051038
|View full text |Cite
|
Sign up to set email alerts
|

Can Follow-Up Examination of Tuberculosis Patients Be Simplified? A Study in Chhattisgarh, India

Abstract: BackgroundEach follow-up during the course of tuberculosis treatment currently requires two sputum examinations. However, the incremental yield of the second sputum sample during follow-up of different types of tuberculosis patients has never been determined precisely.ObjectivesTo assess the incremental yield of the second sputum sample in the follow-up of tuberculosis patients under the Revised National Tuberculosis Control Programme (RNTCP) in Chhattisgarh, India.MethodologyA record review of tuberculosis (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This is similar to reports from other studies from India. [4][5][6]8,13 Missing these would mean not extending the intensive phase of treatment or a delay in switching to the retreatment regimen for a very small number of patients. Both these measures are no longer recommended by the WHO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to reports from other studies from India. [4][5][6]8,13 Missing these would mean not extending the intensive phase of treatment or a delay in switching to the retreatment regimen for a very small number of patients. Both these measures are no longer recommended by the WHO.…”
Section: Discussionmentioning
confidence: 99%
“…3 Previous operational research studies conducted in India and other countries in Africa have found that the proportion of patients with the first sample smear-negative and the second smear-positive (NP) was low, ranging from 0.3% to 4.1%, irrespective of the month of follow-up examination and category of TB patient. [4][5][6][7] There is also evidence to suggest that most of these results, where only one of the two smears are positive, are culture-negative, meaning that there were no viable tubercle bacilli. 8 Based on this evidence, India's Revised National Tuberculosis Control Programme made a national policy decision in 2016 to examine only one sputum specimen during follow-up examinations.…”
mentioning
confidence: 99%
“…Hence, we will also benefit from the savings in cost and time incurred for the laboratory, which can be used for further improving quality of smear microscopy. In a study done in various microscopy centres of the state of Chattisgarh, India in 2012, decreasing the number of sputum examinations during follow-up can reduce the overall laboratory workload by 15% [31]. Therefore, we strongly recommend discontinuation of examining third sample if the first two were confirmed especially in areas where sputum culture could not be done.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the low incremental yield of the second specimen and the potential to reduce laboratory workload and costs for the programme by examining only one specimen. 3 Given the benefits for the patient of eliminating the additional visit required for the second examination, we strongly recommend the following change in global policy: a switch from two specimens to one specimen during follow-up and confirmation of a positive smear by a second positive smear before declaring a patient a bacteriological failure. This is in line with the recommendation of The Union.…”
Section: Public Health Action 2 Vs 1 Specimens During Follow-up 306mentioning
confidence: 99%
“…1,2 Previous operational research from India and other countries has shown that the incremental yield of a second smear was very low, irrespective of the month of f ollow-up and category of TB patient, and have questioned the value of a second smear. [3][4][5] Previous studies have also shown that the specificity of smear microscopy to detect living tubercle bacilli during treatment follow-up is low: more than two thirds of all follow-up smear-positives were culture-negative. [6][7][8][9] In addition, whenever only one of the two smears was positive, they were mainly graded as scanty or '1+ positive', possibly indicating fewer and mostly non-viable bacilli.…”
mentioning
confidence: 99%